2022
DOI: 10.1002/advs.202105517
|View full text |Cite
|
Sign up to set email alerts
|

Triangular Topological 2D Covalent Organic Frameworks Constructed via Symmetric or Asymmetric “Two‐in‐One” Type Monomers

Abstract: Most of the reported covalent organic frameworks (COFs) so far are prepared from highly symmetric building blocks, which to some extent limits the expansion of COF diversity and complexity. Low-symmetric building blocks can be designed through a desymmetrized vertex strategy, which might be used to construct new topological COFs. But reports of COFs constructed by asymmetric building blocks are thus far very rare. Here, a feasible strategy to design asymmetric building blocks for COF synthesis is introduced, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…38 The mentioned concept of "from isomeric monomers to isomeric frameworks" has been extended to the synthesis of isomeric COFs with triangular pores. 39 The above examples demonstrate that the "two-in-one" strategy might be a proven and effective method for the construction of 2D constitutional isomeric COFs. Apart from synthetic solvents, catalysts would be another crucial element for the formation of periodically ordered structures of COFs.…”
Section: Minireviewmentioning
confidence: 94%
“…38 The mentioned concept of "from isomeric monomers to isomeric frameworks" has been extended to the synthesis of isomeric COFs with triangular pores. 39 The above examples demonstrate that the "two-in-one" strategy might be a proven and effective method for the construction of 2D constitutional isomeric COFs. Apart from synthetic solvents, catalysts would be another crucial element for the formation of periodically ordered structures of COFs.…”
Section: Minireviewmentioning
confidence: 94%
“…[16a,b] The varied combinations of different monomers result in various COF structures that now can be found via several online databases. [18] 2D COFs with a planar geometry can be symmetric or asymmetric [19] , exhibiting trigonal, rhombic, tetragonal, hexagonal, or varied pore combinations (e.g., dual-pore Kagome and triple-pore Kagome), as displayed in Figure 1a. These topologies can be controlled using different combinations of monomers.…”
Section: The Design and Synthesis Of Cofsmentioning
confidence: 99%
“…Among them, only a few triangular COFs have been reported that could be ascribed to the limited configuration of building units, although their unique triangular channel makes them special on precise recognition and selective transport. [14] Currently, the triangular COFs [11,12] could only be accessed through the co-polymerization of C 6 -and C 2 -symmetric building blocks or the self-polymerization of C 3 -symmetric monomers (Figure 1a). In addition, Feng et al [13] exploited the desymmetrized vertex design approach through lengthening or shortening the branches of symmetry building blocks (e.g., C 2 , C 6 ) to form the heteroporous triangular COFs, which present the rare example of the super microporous dual-triangle COFs.…”
Section: Introductionmentioning
confidence: 99%